1998
DOI: 10.1021/bi980349n
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Mosaic Virus Disassembly by High Hydrostatic Pressure in Combination with Urea and Low Temperature,

Abstract: We investigated the effect of low temperature and urea combined with high pressure on tobacco mosaic virus (TMV). The evaluation of its aggregation state and denaturation process was studied using gel filtration, transmission electron microscopy, and spectroscopic methods. The incubation at 2.5 kbar induced 18% dissociation, and decreasing of temperature to -19 degreesC promoted additional dissociation to 72%, with stabilization of the dissociation products. Under such conditions, extensive denaturation did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 22 publications
5
45
0
7
Order By: Relevance
“…This finding will be helpful to determine an optimal pressure to treat food products with different pH values. Our observation is consistent with the previous reports for FCV (16) and tobacco mosaic virus (8,51), which were also more resistant to HPP at lower pH. In contrast, a significantly enhanced inactivation of HAV was found in acidic environments (35)(36)(37).…”
Section: Discussionsupporting
confidence: 93%
“…This finding will be helpful to determine an optimal pressure to treat food products with different pH values. Our observation is consistent with the previous reports for FCV (16) and tobacco mosaic virus (8,51), which were also more resistant to HPP at lower pH. In contrast, a significantly enhanced inactivation of HAV was found in acidic environments (35)(36)(37).…”
Section: Discussionsupporting
confidence: 93%
“…11 incubation of the protein with increasing amounts of GndHCl resulted in a significant shift in the center of mass [37,38] and a bathochromic red-shift in the fluorescence emission maximum (from 334 nm to 360 nm), and also in a severe quenching of the fluorescence emission intensity (Figures 2A and 2C). In contrast with the CD results, the GndHCl induced unfolding as monitored by the intrinsic fluorescence unambiguously reveals an intermediate state at the GndHCl concentrations around 2.75 M and 3.5 M (Figure 3).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…CD spectra were measured from samples in 1.0 mm path length quartz cuvettes, and were the average of 16 accumulations, using a scanning speed of 100 nm min - Intrinsic fluorescence spectra were obtained by excitation at 295 nm, and the emission spectra were monitored from 300 to 450 nm. Relevant information about macromolecule conformational flexibility can be obtained by considering the fluorescence spectral center of mass [37,38]. In this case, the fluorescence spectral center of mass (λ cm ) was calculated, for each concentration of chaotropic agents, according to the equation [37,38]:…”
Section: Circular Dichroism Spectroscopy (Cd) Chemical Unfolding Of mentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, virus-urea interaction has been investigated in TMV dissociation and subunit denaturation. Bonafe et al (1998) showed how the apparent free energy associated with denaturation by urea for TMV protein coat was very low, almost null. The apparent urea stoichiometry of dissociation and denaturation of further viral agents has been calculated (Santos et al, 2008).…”
Section: Action Mechanism Of Synthetic Productsmentioning
confidence: 99%